Differential expression of intestinal nutrient transporters and host defense peptides in Eimeria maxima-infected Fayoumi and Ross chickens. (11th July 2018) - Su, S; Miska, K B; Fetterer, R H; Jenkins, M C; Lamont, S J; Wong, E A
Abstract: Fayoumi chickens are believed to be more disease resistant compared to commercial broiler chickens. The objective of this study was to compare mRNA expression of intestinal nutrient transporters, digestive enzymes, and host defense peptides (HDP) between Eimeria maxima -challenged Fayoumi and Ross broiler chickens. At 21 d of age, Ross broilers and Fayoumi lines M5.1 and M15.2 were challenged with 1, 000 E. maxima oocysts. Control birds were not challenged. Duodenum, jejunum, and ileum were sampled (n = 6) at 7 d post challenge. Gene expression was analyzed using relative quantification PCR. Data were analyzed by ANOVA and significance level was set at P < 0.05. There was numerical, but not statistically significant, differential weight gain depression for Ross (15%) and Fayoumi lines M5.1 (21%) and M15.2 (22%) and significant line-specific changes in gene expression. For nutrient transporters, there was downregulation of mRNA for the brush border membrane, amino acid transporters b 0, + AT/rBAT, B o AT, and EAAT3 in different segments of the small intestine of Ross and both lines of Fayoumi chickens, indicating that E. maxima challenge likely caused a decrease in nutrient uptake. For HDP, there was downregulation of avian beta defensin (AvBD) 1, 6, 10, 12, and 13 mRNA in the jejunum of the 2 Fayoumi lines, but no change in the Ross broilers. In the duodenum, there was upregulation of AvBD10 mRNA in the Ross and both Fayoumi lines and additionally upregulation of AvBD11, 12, and 13 mRNA in only Fayoumi line M15.2. Liver expressed antimicrobial peptide 2 (LEAP2) mRNA was downregulated in the duodenum and jejunum of Ross and Fayoumi line M5.1 but not in Fayoumi line M15.2. The homeostatic, non-challenged levels of AvBD mRNA were greater in Fayoumi line M15.2 than Ross and Fayoumi line M5.1 in the duodenum and ileum. This study demonstrates tissue- and genetic line-specific transcriptional responses to E. maxima, highlights novel potential candidate genes for response to coccidiosis, and confirms a role for several previously reported genes in response to coccidiosis.